DECOMPOSITIONS OF COMPLETE GRAPHS INTO KAYAK PADDLES - Froncek, Dalibor; Tollefson, Leah (IndoMS, 2011)
A canoe paddle is a cycle attached to an end-vertex of a path. It was shown by Truszczynski that all canoe paddles are graceful and therefore decompose complete graphs. A kayak paddle is a pair of cycles joined by a path. We prove that the complete graph Ksub2n+1/sub is decomposable into kayak paddles with in/i edges whenever at least one of its cycles is eve.DOI :Â http://dx.doi.org/10.22342/jims.0.0.17.39-44